Beatrice Lane Suzuki (1875–1939) - Judith Snodgrass (St Andrews Encyclopaedia of Theology)
Beatrice Lane Suzuki was the American born wife of renowned Zen scholar Daisetz Teitaro Suzuki. Until very recently, nothing beyond this had been written about her. She was, however, also a very significant figure in introducing Japanese Buddhism to the West, a partner in the mission to making Mahāyāna Buddhism better understood in the West. This paper begins by looking at her early life to establish what she brought to the partnership, and the spiritual search that brought her to Mahāyāna Buddhism. The body of the paper analyses her contribution to Western knowledge of Buddhism: as a founding editor of the pioneering journal of Mahāyāna Buddhism, the Eastern Buddhist, and as a prolific author on Buddhism in her own right. It shows the distinctive contribution she made through her commitment to the Bodhisattva vows as a path to spiritual development in modern, secular life, and as a solution to the world problems so apparent in the interwar period in which she wrote.